2016
DOI: 10.1007/s11764-016-0525-8
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer survivors’ quality of life: a systematic review

Abstract: OC survivors experience a wide range of sequelae that may persist for a long time and negatively impact QOL. Further large-scale research is needed to fully understand problems that have significant effects on QOL, in order to develop interventions and treatments suitable for women at need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 51 publications
1
50
0
1
Order By: Relevance
“…Sexual functioning is an important yet underreported part of a woman's quality of life. Previous studies have shown that women often experience serious disruptions in sexual function after treatment for gynaecological cancer . This can cause women to feel less interested in sexual relations, with negative impact on their relationship with partners .…”
Section: Introductionmentioning
confidence: 99%
“…Sexual functioning is an important yet underreported part of a woman's quality of life. Previous studies have shown that women often experience serious disruptions in sexual function after treatment for gynaecological cancer . This can cause women to feel less interested in sexual relations, with negative impact on their relationship with partners .…”
Section: Introductionmentioning
confidence: 99%
“…In the recently published systematic review [10] there was argued that despite the persistence of psychological and physical symptoms, treatment sequelae, sexual problems, and fear of recurrence in some survivors, most studies demonstrated that OC survivors generally have good QOL compared to healthy women. Sereika S .M.…”
Section: Discussionmentioning
confidence: 99%
“…Women with ovarian cancer have some or all of these experiences and other related experiences. Women with ovarian cancer report the significant physical and emotional impact of the disease on quality of life (147)(148)(149)(150)(151) and the needs of cancer patients often go unmet. (151)(152)(153) Supporting women effectively during the diagnostic, treatment and post treatment phases involves managing the physical, psychological and social impact of the disease and its treatment.…”
Section: Support Needs For Women With Ovarian Cancermentioning
confidence: 99%